Mobility of Metals in Sediments Contaminated with Historical Mining Wastes: Example from the Tri-State Mining District, USA - Mélida Gutiérrez; Zachary J. Collette; Anastasia M. McClanahan; Kevin Mickus (Soil Systems, 2019)
The Tri-State Mining District (TSMD) of Kansas, Missouri, and Oklahoma was a world class zinc (Zn) and lead (Pb) producer. Mining ceased in the 1950s, leaving behind a large amount of mine wastes. Although much of the affected areas have been remediated, stream sediments may still contain toxic levels of these metals. The mobility of the metals was determined for sediment samples from Turkey Creek, Missouri. The median values of the metal content were 2700 mg/kg Zn, 161 mg/kg Pb, and 10.8 mg/kg Cd. These concentrations marginally surpass the sediment quality guidelines that differentiate between toxic and nontoxic conditions. Mobility was determined by sequential extraction of two phases—bioavailable and Fe-oxides. The fraction of the metal available to biota was 7.7% for Zn, 5.0% for Cd, and 0.4% for Pb, whereas the Fe-oxide fraction retained 25% of Zn, 21% of Pb, and 35% Cd. These values roughly agree with the values reported for other areas of the TSMD. Fractionation provides an estimate of the amount of metal available at the present conditions and gives the amount of metal available should the pH and/or Eh vary. The methodology puts an emphasis on ecosystem health and can be applied to other areas where Zn–Pb concentrations in soils and sediments are a concern.